2009
DOI: 10.1287/orsc.1080.0379
|View full text |Cite
|
Sign up to set email alerts
|

Do Workgroup Faultlines Help or Hurt? A Moderated Model of Faultlines, Team Identification, and Group Performance

Abstract: I n this study we examine a moderated model of group faultlines, team identification, and group performance outcomes. We extend research on faultlines by showing how different faultline bases (social category and information-based faultlines) may have differential effects on the performance of groups. In addition to faultline strength (the extent of demographic alignment across members within a group), we examine the distance between faultline-based subgroups (e.g., two members of age 20 are closer in age to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
568
7
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 380 publications
(602 citation statements)
references
References 96 publications
(130 reference statements)
22
568
7
5
Order By: Relevance
“…Molleman, 2005). Speaking more to the categorization dynamics underlying faultlines, Bezrukova et al (2009) showed that faultlines are more disruptive the greater the difference between subgroupings (cf. comparative fit), and also obtained some evidence that faultlines may be less problematic the more members identify with the team (which was also interpreted in terms of comparative fit).…”
Section: Human Relations 64(3)mentioning
confidence: 99%
“…Molleman, 2005). Speaking more to the categorization dynamics underlying faultlines, Bezrukova et al (2009) showed that faultlines are more disruptive the greater the difference between subgroupings (cf. comparative fit), and also obtained some evidence that faultlines may be less problematic the more members identify with the team (which was also interpreted in terms of comparative fit).…”
Section: Human Relations 64(3)mentioning
confidence: 99%
“…While some studies suggest that subgroups also have positive effects for team members [10,12], the majority highlights their negative consequences. In general, any type of faultline may have both, positive and negative impacts [13].…”
Section: Faultlines and Subgroupsmentioning
confidence: 99%
“…In general, any type of faultline may have both, positive and negative impacts [13]. Positive effects of subgroups are mainly found related to knowledge-based subgroups [10,12]. They have the advantage that they bring different forms of knowledge into one team [12].…”
Section: Faultlines and Subgroupsmentioning
confidence: 99%
See 2 more Smart Citations